Bilanthanide Metal–Organic Frameworks for Instant Detection of 17β‐Estradiol, a Vital Physiological Index. Issue 5 (4th October 2021) - Guo, Yifan; Han, Zongsu; Min, Hui; Chen, Zhonghang; Sun, Tiankai; Wang, Liang; Shi, Wei; Cheng, Peng
Abstract : Bilanthanide metal–organic frameworks (MOFs) have promising sensing applications for specific molecules because enhanced sensing functions can be achieved by the dual emissions from bilanthanide centers. In general, chemical mixture or physical mixture of two lanthanide MOFs can both produce dual emissions. However, the advantages of chemical mixture over physical mixture of lanthanide MOFs as sensing materials are not experimentally demonstrated in detail. Herein, a bilanthanide MOF‐based luminescent sensor of NKU‐103(EuTb) synthesized by mixed‐lanthanide strategy for the identification of 17β‐estradiol, a vital diagnostic clinical biomarker, is reported. The dual emission of NKU‐103(EuTb) is able to effectively remove systematic errors, confirmed by varying the slit width, the excitation wavelength, and the concentration. The quenching efficiency ratio and shift distance of Commission Internationale de l'É clairage (CIE) coordinates of NKU‐103(EuTb) are higher than the physical mixture of NKU‐103(Eu) and NKU‐103(Tb), which demonstrates for the first time the superiority of MOF‐based sensing materials by the chemical mixed‐lanthanide strategy. Abstract : With the addition of 17β‐estradiol, a vital diagnostic clinical biomarker, the quenching efficiency ratio and the shift distance of Commission Internationale de l'É clairage (CIE) coordinates of the chemically mixed bilanthanide metal–organic framework (MOF) are higher than that of the physically mixed lanthanide MOFs, which demonstrates the superiority by the mixed‐lanthanide strategy for MOF‐based sensing material.